The Relationship between Psychological Capital and Flourishing in the Development of Psychological Well-being of Entrepreneurial Students in Higher Education - Dio Gustama Mulyono; Olievia Prabandini Mulyana (Al-Qalam Institue, 2025)
Changes in the global economic structure and the acceleration of digitalization have led to increasingly fierce competition in the job market, requiring students to have strong psychological readiness to face academic pressures and business challenges. In this context, psychological capital is a crucial factor that can support psychological well-being, or flourishing, for students engaged in entrepreneurial activities. This study aims to determine the relationship between psychological capital and flourishing in entrepreneurial students at the higher education level. The study used a quantitative correlational approach with a sample of 122 students from Surabaya State University selected through a purposive sampling technique. Data were collected using the CPC-12 and PERMA-Profiler, then analyzed using the Spearman correlation test. The results showed a positive and significant relationship between psychological capital and flourishing (ρ = 0.360; p < 0.001). This finding indicates that the higher the self-efficacy, hope, optimism, and psychological resilience of students, the higher their perceived level of psychological well-being. This study provides practical implications for universities to develop psychological capital strengthening programs to improve mental readiness, academic engagement, and student business success.